HARA N P DAN K SECARA KUALITATIF DISEKITAR PERAKARAN TANAMAN JAGUNG (Zea Mays L) DI DESA TATELU RONDOR KECAMATAN DIMEMBE KABUPATEN MINAHASA UTARA - Novita Mampioper; Jailani Husain; Djoni Kaunang (Universitas Sam Ratulangi, 2019)
ABSTRACT The purpose of this study was to determine the level of nutrient availability, N P and K around corn plants. The results of this study found that the element of nitrogen in the soil around the roots showed relatively low. The element of phosphorus around the roots is moderate and the phosphorus in the soil around the mixed roots is moderate. The element of potassium around the roots is low to high and tanh around the roots are mixed, the potassium content is above the potassium deficiency. Keyword: Hara, N, P, And K, Around Maize Planting, Tatelu Rondor.